Evaluación de los parámetros productivos en pollos de engorde, utilizando larvas de moscas domesticas (musca domestica l) como suplemento alimenticio. - Prado Ortega, Andrea Del Cisne; Troya Cabrera, Margorie Etelvina (Machala : Universidad Técnica de Machala, 2024)
The objective of this work was "Evaluation of productive parameters in broiler chickens using house fly larvae as a dietary supplement" analyzed the viability of including larvae as an alternative source of protein to reduce costs and promote sustainability in poultry farming. Parameters such as growth, feed conversion, economic viability and meat quality were evaluated in 160 chickens under four treatments (0%, 3%, 6% and 10% inclusion of larvae). The results indicated that the inclusion of larvae did not negatively affect growth or feed conversion. Economically, the treatment with 6% was sustainable, and the 6% treatment stood out in the sensory quality of the meat, considered softer and with better flavor. This shows that larvae are a viable alternative in poultry feeding. In conclusion, housefly larvae are an innovative and sustainable solution for chicken production, reducing costs without compromising quality or productivity. Additional studies are suggested to explore more benefits on gut health and large-scale production.
El objetivo de este trabajo fue "Evaluación de los parámetros productivos en pollos de engorde utilizando larvas de moscas domésticas como suplemento alimenticio" analizó la viabilidad de incluir larvas como fuente alternativa de proteína para reducir costos y promover la sostenibilidad en la avicultura. Se evaluaron parámetros como crecimiento, conversión alimenticia, viabilidad económica y calidad de la carne en 160 pollos bajo cuatro tratamientos (0%, 3%, 6% y 10% de inclusión de larvas). Los resultados indicaron que la inclusión de larvas no afectó negativamente el crecimiento ni la conversión alimenticia. Económicamente, el tratamiento con 6% fue sostenible, y el de 6% destacó en la calidad sensorial de la carne, considerada más suave y de mejor sabor. Esto demuestra que las larvas son una alternativa viable en la alimentación avícola. En conclusión, las larvas de mosca doméstica son una solución innovadora y sostenible para la producción de pollos, reduciendo costos sin comprometer la calidad ni la productividad. Se sugiere realizar estudios adicionales para explorar más beneficios en la salud intestinal y la producción a gran escala.
Keywords: LARVAS; PROTEINA; CALIDAD; CONVERSION ALIMENTICIA